Pengaruh Jumlah Penduduk, PDRB, dan Rata-Rata Lama Sekolah terhadap Tingkat Pengangguran Terbuka di Kabupaten/Kota Provinsi Kalimantan Selatan Tahun 2017-2021 - Farika Aditya Ningsih, Siti; Pahlevi, Khairi (PPJP ULM, 2024)
This study aims to analyze the effect of Population, GRDP, and Average Years of Schooling on the Open Unemployment Rate in the Regency/ City of South Kalimantan Province in the 2017-2021 period. The method of analysis used is panel data regression analysis using Eviews 12 software. Data collection is carried out from official sources such as the Central Statistics Agency (BPS) and other related agencies. The results of the study: (1) Population, GRDP, and Average Years of Schooling simultaneously affect the Open Unemployment Rate in the Regency/City of South Kalimantan Province. (2) Total population and GRDP partially have a significant effect on the Open Unemployment Rate, while Average Years of Schooling has no effect on the Open Unemployment Rate in the Regency/City of South Kalimantan Province. (3) Total Population is the most dominant variable affecting the Open Unemployment Rate.